Review on pineapple leaf fibre (PALF) – polymer composites - Mohamed Yusoff, Mohd Zuhri; Salit, Mohd Sapuan; Hamdan, H. I. M. (2009)
Natural fibres are currently has been attracting the researcher, academicians and industries in order to become a green environmental technology. Pineapple leaf fibre is one of the attraction in this natural fibre composite. Mechanical properties of PALF polymer composites carried out by various researchers are discussed in this paper. Thermosetting and thermoplastic resins have been used as matrices in these PALF composites.